Some Psychometric Properties of Lithuanian Thinking and Language Dysfunction Scale (TALD) - Petraškaitė, Karolina; Grigutytė, Neringa (Psichologija, 2023)
Thought disorder is one of the main symptoms of schizophrenia, although signs of it are also found in other disorders, such as schizoaffective disorder or depression, so it is important to find the best ways to assess symptoms and use them to differentiate between different disorders. Thought and Language Dysfunction Scale (TALD) is one of the newest and empirically based instruments that can help assess not only objectively observed but also subjectively expressed signs of thought disorder in various mental illnesses. This article aims to analyse some psychometric characteristics of the Lithuanian version of TALD in different psychiatric disorders. 129 individuals participated in the study (73 men, 56 women, age M = 34.28, SD = 9.95), of which 39 had schizophrenia, 27 schizoaffective disorder, 31 depression diagnoses, and 32 belonged to the control group. Using exploratory and confirmatory factor analysis, four thought disorder symptom factors were confirmed, which reflect dimensions of positive, negative, objective, and subjective symptoms. The scale has appropriate reliability characteristics. The results of both the total score and the different dimensions are significantly higher in the clinical groups compared to the controls. The results of all dimensions and the overall assessment allow excellent separation of those who suffer from mental health disorders from those who not, and the objective positive symptoms can differentiate schizophrenia or schizoaffective patients from depression ones the most effectively. Although further research on psychometric properties is important, the instrument may be useful when used in conjunction with other research methods in the psychodiagnostics.